Contributions to the psychology of consumerism: education and consumers´ defense - Fuentes, Nhora Constanza (2016)
This study aims at determining the contributions of psychology to the phenomenon of consumerism. To this end, we contextualize the theoretical framework, considering current specific societal circumstances, as well as legal aspects both in the international and the Colombian national contexts. A review of the literature allows us to identify specific contributions of the psychology of consumerism. Finally, we discuss the active role psychology should have in this topic, the psychological factors that mediate in the process and the characteristics psychologists interested in the psychology of consumerism should have.